Penggunaan SMS Gateway pada Sistem Informasi Pengasuhan dan Pengajaran Pesantren Berbasis Web - Zulfan Khairil Simbolon; Nurul Husna; Huzaeni Huzaeni (VOCATECH: Vocational Education and Technology Journal, 2023)
AbstractNowadays information systems are widely chosen as media to help human activities in a way that is more efficient both in energy and in time. The registry of modern boarding schools Tgk. Chiek Oemar Diyan, where the application for the nurturing and education section of boarding schools is still done manually which often caused the error, also constraints for the parents to know student's progress during the school time. The purpose of the information system for tgk. Chiek Oemar Diyan Islamic Boarding School is to help facilitate the nurturing and teaching section to manage the students data so as to reduce the the possibility of error or likelihood of confusion. the system is also equipped with a gateway text or well known as SMS Gateway using SMS Gateway Me and EnvayaSMS as an intermediary communication of the boarding schools and the parents to answer the insecurities of the parents related to the students. The SMS Gateway feature is chosen to reach all circles of parents, this feature will provide information regarding violations and permits that is carried out by the students, the parents can also convey the necessary complaints. The The nurturing and teaching information system using this web-based gateway text resulting information system that helped alleviate the performance of the present day of the nurturing and teaching section of modern boarding schools Tgk. Chiek Oemar Diyan and was also a means of communicating with the parents. Key Words Information system, SMS Gateway, data collection, Communication. AbstrakSistem informasi banyak dipilih sebagai media untuk membantu kegiatan manusia agar lebih efisien dari segi tenaga waktu. Selama ini pendataan pada Pesantren Modern Tgk. Chiek Oemar Diyan untuk bagian pengasuhan dan bagian pengajaran masih dilakukan secara manual sehingga menimbulkan kekeliruan, juga kendala bagi wali santri untuk mengetahui perkembangan santri selama dipesantren. Tujuan Sistem Informasi untuk Pesantren Modern Tgk Tgk. Chiek Oemar Diyan adalah membantu memudahkan pihak pengasuhan dan pengajaran dalam mengelola data santri sehingga mengurangi kemungkinan kekeliruan, sistem ini dilengkapi dengan fitur SMS Gateway menggunakan SMS Gateway Me dan EnvayaSMS sebagai perantara komunikasi pihak pesantren dan wali santri untuk menjawab kegelisahan wali santri selama santri dipesantren. SMS Gateway dipilih agar bisa menjangkau semua kalangan wali santri, fitur ini akan memberikan informasi terkait pelanggaran dan perizinan yang dilakukan, wali santri dapat melakukan pengecekan terhadap jadwal libur juga menyampaikan keluhan yang diperlukan. Sistem Informasi Pengasuhan dan Pengajaran menggunakan SMS Gateway berbasis Web ini memberikan hasil akhir berupa sistem informasi yang membantu meringankan kinerja bagian Pengasuhan dan Pengajaran Pesantren Modern Tgk. Chiek.Oemar Diyan juga sebagai sarana komunikasi pihak pesantren dengan wali santri. Kata Kunci  Sistem Informasi, SMS Gateway, pendataan, komunikasi.